(untitled) (International Journal of Engineering and Computer Science, 2015)
Now a days Cloud computing is a very popular and rising technology using which it is easy to access on-demand network resources in a convenient manner. Mobile cloud computing is the availability of cloud computing services in a mobile ecosystem. Mobile cloud computing means services are provided by a cloud and anyone can accessed through mobile platforms. This paper introduce C/C++/JAVA compilers which make it easy to compile and execute programs anytime anywhere by using their android smartphone. The main aim of this application is that their is no need to install any software/compilers in their phones. Anyone can access these C/C++/JAVA compilers remotely through network.